Alleviating Anxiety Through the Abecedarian: On Supporting New Doctoral Students (LEARNing Landscapes, 2019)
This paper seeks to offer insights and gentle suggestions for higher education leaders, particularly those teaching and supervising new doctoral students. Graduate students experience stress and anxiety, making entering the academic sphere an often emotionally taxing move. In response, a great deal of research examines how university faculty might ease this transition into a particularly intimidating, rigorous space. As such, this poetic offering invites education leaders who interact with new doctoral students to consider an abecedarian written in the spirit of capturing the potential needs and wants of early scholars navigating their PhD programs at the beginning of the journey.
Keywords: abecedarian; anxiety; doctoral students; graduate school; higher education; mental health; PhD; poetic inquiry